Characterization of an Experimental Vaccine for Bovine Respiratory Syncytial Virus - Hägglund, Sara (American Society for Microbiology, 2014)
Bovine respiratory syncytial virus (BRSV) and human respiratory syncytial virus (HRSV) are major causes of respiratory disease in calves and children, respectively, and are priorities for vaccine development. We previously demonstrated that an experimental vaccine, BRSV-immunostimulating complex (ISCOM), is effective in calves with maternal antibodies. The present study focuses on the antigenic characterization of this vaccine for the design of new-generation subunit vaccines. The results of our study confirmed the presence of membrane glycoprotein (G), fusion glycoprotein (F), and nucleoprotein (N) proteins in the ISCOMs, and this knowledge was extended by the identification of matrix (M), M2-1, phosphoprotein (P), small hydrophobic protein (SH) and of cellular membrane proteins, such as the integrins α(V)β(1), α(V)β(3), and α(3)β(1). The quantity of the major protein F was 4- to 5-fold greater than that of N (∼77 μg versus ∼17 μg/calf dose), whereas G, M, M2-1, P, and SH were likely present in smaller amounts. The polymerase (L), M2-2, nonstructural 1 (NS1), and NS2 proteins were not detected, suggesting that they are not essential for protection. Sera from the BRSV-ISCOM-immunized calves contained high titers of IgG antibody specific for F, G, N, and SH. Antibody responses against M and P were not detected; however, this does not exclude their role in protective T-cell responses. The absence of immunopathological effects of the cellular proteins, such as integrins, needs to be further confirmed, and their possible contribution to adjuvant functions requires elucidation. This work suggests that a combination of several surface and internal proteins should be included in subunit RSV vaccines and identifies absent proteins as potential candidates for differentiating infected from vaccinated animals.